Answers

2015-10-17T17:46:39+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(k - 3)  x  + 3 y = k     --- (1) 
 k  x  + k  y = 12        --- (2)

(1) * k  - (2) * 3  =>
     k(k - 3) x  - 3 k x = k² - 36
     x =  (k² - 36) / (k² - 6 k)  =  (k - 6) (k + 6) / [ k (k - 6) ]

     x = (k + 6) / k        if  k ≠ 6
   There is only one solution.

If k = 6, then:  the equations are :
      3 x + 3 y = 6
      6 x + 6 y = 12
Then there are infinite solutions.

====================
The determinant of the following matrix of the coefficients of x and y:

|  k-3      3    |  
|  k        k    |

is equal to:    k² - 3 k - 3 k     =  k²  - 6 k
        Determinant = 0  for   k = 0  and  k = 6.

check  if the equations given have  infinite solutions for these two values of k.

1 5 1
click on thanks button above ;;select best answer